A hybrid discontinuous voltage controller for DSTATCOM applications - Goyal, S.; Ghosh, Arindam; Ledwich, G. (Institute of Electrical and Electronics Engineers ( IEEE ), 2008)
This paper proposes a hybrid discontinuous control methodology for a voltage source converter (VSC) based distribution static compensator (DSTATCOM) connected to a 3-phase distribution system. It is assumed that the DSTATCOM controls the point of common coupling (PCC) voltage. An LC output filter is connected at the output of the VSC. With the help of both filter inductor current and filter capacitor voltage control, the voltage across the filter capacitor is controlled. Based on the voltage error, the control is switched between voltage and current control mode. In this scheme, an extra diode state is used that makes the VSC output current discontinuous. This diode state reduces the switching losses because half of the total switching occurs at nearly zero converter current. The effects of different source conditions on voltage at PCC are studied. Voltage angle at PCC is controlled using a PI controller. Simulation studies are performed using PSCAD to validate the efficacy of the proposed controller.